Peran Intelijen Dalam Assessment Deradikalisasi Terhadaap Ancaman Terorisme Untuk Meningkatkan Ketahanan Wilayah (Studi Pada Napiter Dan Mantan Napiter di Propinsi Jawa Barat) - Irawan, Dian Dwi (Jurnal Ketahanan Nasional, 2024)
ABSTRACT Terrorism posed a real threat to regional resilience of the West Java region. One of the challenges in addressing terrorism was that deradicalization efforts often fall short, particularly during the assessment phase. This research aimed to sheded light on the role of intelligence in the assessment of deradicalization programs for convicted and ex-convicted terrorists.The study adopts a descriptive qualitative approach. Researchers classified terrorism convicts and ex-convicts based on their responses to deradicalization programs, to identified priorities for intelligence support in the assessment process. Primary data in the form of notes from observations and interviews with eleven former terrorism convicts in West Java was used, along with secondary data from previous research and online news sources.This was the first study on intelligence assessment in the context of deradicalization efforts and was therefore expected to provided valuable insights in this area. The research findings indicated that the West Java region was particularly vulnerable to terrorism, with a concerning number of recidivism cases. Based on the classification of terrorist convicts and ex-convicts in this study, there were two categories of individuals who required more in-depth assessment, supported by intelligence information. Intelligence could help identified opportunities for deradicalization and carried out thorough assessments that would otherwise be difficult to obtained. Proper assessment was crucial for effective deradicalization and reducing the likelihood of terrorist recidivism. This wouldl ultimately increase regional resilience against the threat of terrorism.